2021
DOI: 10.18280/ts.380102
|View full text |Cite
|
Sign up to set email alerts
|

Depression Detection Based on Geometrical Features Extracted from SODP Shape of EEG Signals and Binary PSO

Abstract: Late detection of depression is having detrimental consequences including suicide thus there is a serious need for an accurate computer-aided system for early diagnosis of depression. In this research, we suggested a novel strategy for the diagnosis of depression based on several geometric features derived from the Electroencephalography (EEG) signal shape of the second-order differential plot (SODP). First, various geometrical features of normal and depression EEG signals were derived from SODP including stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 56 publications
0
33
0
2
Order By: Relevance
“…This enhances the generalizability but increases the risk that features of the clinical EEG recording environment might impact results. Recently, progress was made to accurately classify healthy subjects and patients with depression and schizophrenia by automated geometrical feature extraction of EEG signals [64][65][66][67][68][69][70][71][72][73][74] . The accuracy of these methods to separate these groups is non-inferior to our presented method, although their algorithm uses multiple feature extractions and thus the physiological interpretation is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…This enhances the generalizability but increases the risk that features of the clinical EEG recording environment might impact results. Recently, progress was made to accurately classify healthy subjects and patients with depression and schizophrenia by automated geometrical feature extraction of EEG signals [64][65][66][67][68][69][70][71][72][73][74] . The accuracy of these methods to separate these groups is non-inferior to our presented method, although their algorithm uses multiple feature extractions and thus the physiological interpretation is difficult.…”
Section: Discussionmentioning
confidence: 99%
“…Summation of triangle area using consecutive points (STA) For every three consecutive points of the shape of the Poincaré plot in 2-D space, there is only one triangle. To measure the covered area by shape in 2-D space, STA is defi ned, which can be formulated as follows (28,30): where m is the number of Poincaré plot arrays (see Equation 3); [X (i) Y (i)], [X (i+1) Y (i+1)] and [X (i+2) Y (i+2)] indicate how to coordinate three consecutive points of Poincaré plot shape in a 2-D space. Figure 5 shows the STA as a geometrical feature.…”
Section: Standard Descriptors Of 2-d Projection (Std)mentioning
confidence: 99%
“…The drawback of the RPS technique lies in the time-consuming nature of the procedure, particularly because the MI and FNN calculations are highly burdensome. Although SODP, unlike RPS, can illustrate the EEG signals without any parameter calculation, SODP illustrates the variability of the signal, not the signal itself (23,30). In other words, SODP cannot illustrate the complex nature of the signal (12).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When effective feature selection is performed on the EEG, the support vector machine (SVM), linear discriminant analysis (LDA), naive Bayes (NB), k-nearest neighbors (kNN), and decision tree (D3) can be used to make predictions with better results [ 27 ]. Akbari et al suggested a novel strategy for the diagnosis of depression based on several geometric features derived from the EEG signal shape of the second-order differential plot (SODP) [ 28 ]. With the development of deep learning, many researchers are using deep network models for the detection of depression.…”
Section: Introductionmentioning
confidence: 99%